ISLAM NUSANTARA: Studi Epistemologis Dan Kritis - Alma’arif, Alma’arif (Universitas Islam Negeri Raden Intan Lampung, 2015)
Religion and culture are two different things but very closely related. The majority of people are very complicated or quite difficult to distinguish the absolute religion, and which culture becomes an expression well as vehicle and relatively it. Of course, the inability of a person to distinguish lack of clarity is causing chaos in thinking epistemological side, chaos in the sense of hierarchy where the value associated with the higher values and the lower values, which is absolute and which are relatively. Departing from these problems, using the historical- anthropological approaches and methods of analysis-critical then this article tries to discuss about archipelagic Islam. The main stression is in the epistemological analysis of archipelagic Islam. Critical analysis carried out toward archipelagic Islam is expected to map it which aims unveil what should be retained and that what should be deconstructed. The conclusion from this study is the dialectics between religions that have moral and universal values with the culture and traditions of the people of Indonesia to form a distinctive style of Indonesian Islam is commonly called archipelagic Islam. Archipelagic Islam is legitimate from the standpoint of epistemological. Critical analysis of archipelagic Islam yield maping, on which should be kept and which should be deconstructed. Among the things that should be maintained is the spirit of archipelagic Islam tolerance in diversities, appreciation of good traditions and elasticity in reading of religious texts. The things that should be deconstructed is the doctrine of al- Ghazali in hostile philosophy and natural sciences and a strong guard toward myths and mystical archipelagic Islam that impede progress and civilization.